Approaching the upper bound of load capacity: Functional grading with interpenetrating polymer networks. (5th January 2018) - Chen, Zhong; Li, Wenlong; Negahban, Mehrdad; Saiter, Jean-Marc; Delpouve, Nicolas; Tan, Li; Li, Zheng
Abstract: Functional grading is used to push the load capacity of parts to within the upper bound of what is theoretically possible. Using interpenetrating polymer networks (IPNs), a material system used to achieve grading during printing, the possibility of producing realistic grading of acrylate/epoxy IPNs is studied with the goal of increasing load capacity to within the limit of what is possible, and substantially beyond the load capacity possible with any uniform mixture of this IPN system. In the process, an upper bound of possible improvement is established for a plate with a circular hole in tensions, and the grading for this plate is adjusted to give an optimal load capacity near this upper bound. The optimal grading proposed is different from that shown in previous work due to the simultaneous consideration of both the effect of grading on elastic moduli and on the ultimate stress. A similar study was done for an L-shaped bracket indicating similar improvements over uniform brackets. Graphical abstract: Highlights: Optimal grading by combined consideration of elastic moduli and ultimate stress Evaluation of grading that provides load capacity near the upper bound of possible improvement Adaptation of solution scaling to significantly reduce the time to obtain optimal grading Implementation for grading based on interpenetrating polymer networks of acrylate and epoxy